The best way to combine the two sentences into a single sentence is:
Because of its poisonous bite, the asp is a dangerous snake.
An asp has a poisonous bite.
Which is the best way to combine the two sentences into a single sentence?
(1 point)
Responses
Because of its poisonous bite, the asp is a dangerous snake.
Because of its poisonous bite, the asp is a dangerous snake.
Whereas the asp is a dangerous snake, it has a poisonous bite.
Whereas the asp is a dangerous snake, it has a poisonous bite.
Although the asp is a dangerous snake, it has a poisonous bite.
Although the asp is a dangerous snake, it has a poisonous bite.
Despite its poisonous bite, the asp is a dangerous snake.
5 answers
The best way to combine the two sentences into a single sentence is:
Because of its poisonous bite, the asp is a dangerous snake.
To solve the equation \( 5^{2x + 1} = 25^{-1} \), we can start by rewriting \( 25 \) as \( 5^2 \):
\[ 25^{-1} = (5^2)^{-1} = 5^{-2} \]
Now, we can rewrite the equation as:
\[ 5^{2x + 1} = 5^{-2} \]
Since the bases are the same, we can set the exponents equal to each other:
\[ 2x + 1 = -2 \]
Now, solve for \( x \):
Subtract 1 from both sides: \[ 2x = -2 - 1 \] \[ 2x = -3 \]
Divide by 2: \[ x = -\frac{3}{2} \]
Thus, the solution is:
\[ \boxed{-\frac{3}{2}} \]
Let’s re-examine the equation step by step to find the correct solution.
The given equation is:
\[ 5^{2x + 1} = 25^{-1} \]
We know that \(25\) can be expressed as \(5^2\), so we rewrite \(25^{-1}\):
\[ 25^{-1} = (5^2)^{-1} = 5^{-2} \]
Thus, we have:
\[ 5^{2x + 1} = 5^{-2} \]
Since both sides of the equation have the same base, we can equate the exponents:
\[ 2x + 1 = -2 \]
Now, solving for \(x\):
\[ 2x = -2 - 1 \] \[ 2x = -3 \]
\[ x = -\frac{3}{2} \]
However, based on your statement of solutions being \(5\) and \(-2\), let’s verify those results against the original equation:
Starting over from \(5^{2x+1} = 25^{-1}\) or \(5^{2x + 1} = 5^{-2}\):
This gives the exponent equation:
Case 1:
If \(2x + 1 = -2\): \[ 2x + 1 = -2 \implies 2x = -3 \implies x = -\frac{3}{2} \]
This indicates \(x = -\frac{3}{2}\) is indeed a correct solution.
Case 2: If you want to equate to \(x\) being \(5\):
If you're asserting solutions of \(5\) or \(-2\), let's verify it simply through testing:
If \(x = 5\): \[ 5^{2(5)+1} = 5^{10 + 1} = 5^{11} \] However, \[ 25^{-1} = 5^{-2} \text{ is clearly incompatible with } 5^{11}. \]
If \(x = -2\): \[ 5^{2(-2) + 1} = 5^{-4 + 1} = 5^{-3} \text{ still misaligns.} \]
The equation is resolved as shown, confirming \(x = -\frac{3}{2}\) stands correct.
If another formulation or reinterpretation is in need, please clarify!